Microencapsulation techniques for cannabinoids: pharmaceutical approaches, technological challenges, and formulation perspectives - Aleksandrov, Mihail; Maksimova, Viktorija; Smilkov, Katarina (Archives of Pharmacy, 2026)
Microencapsulation is a widely applied strategy for protecting bioactive compounds by entrapping them within a polymeric or lipid-based shell, thereby enhancing their stability and enabling controlled release. In recent years, the growing number of applications of cannabinoids has driven increasing interest in microencapsulation as a strategy to overcome challenges related to poor aqueous solubility, chemical instability, and limited bioavailability. The aim of this review is to summarize and evaluate commonly employed microencapsulation techniques for obtaining cannabinoid delivery systems. A systematic literature search was conducted using the PubMed, SCOPUS, EBSCO, and Embase databases, resulting in the selection of over 50 original research articles and reviews. The search strategy employed combinations of keywords including cannabis AND microencapsulation methods, cannabinoids AND microencapsulation techniques, hempseed oil AND spray-drying OR coacervation technology, and cannabis industry AND microencapsulation. The findings indicate that the most frequently investigated microencapsulation techniques for cannabinoids include spray-chilling, spray-cooling, fluidized-bed coating, liposomal entrapment, extrusion, freeze-drying, coacervation, and emulsification. These techniques differ in their encapsulation efficiency, scalability, particle size distribution, and suitability for specific delivery routes. Overall, microencapsulation has demonstrated significant potential to improve the physicochemical stability of cannabinoids, protect them from environmental degradation, and enable controlled or targeted release. In conclusion, microencapsulation represents a promising and rapidly evolving approach for the development of advanced cannabinoid formulations, offering innovative solutions for enhanced stability, defined delivery performance, leading to potential of therapeutic applicability.
Keywords: cannabinoids; controlled release; encapsulation techniques; microencapsulation; stability enhancement